AORTIC POST-RESISTANCE EXERCISE HYPOTENSION IN PATIENTS WITH PERIPHERAL ARTERY DISEASE - Correia,Marilia de Almeida (2018)
ABSTRACT Introduction: A single session of resistance training decreases brachial blood pressure (BP) in patients with peripheral artery disease (PAD). However, it is not known whether similar responses occur in aortic BP, which is a better predictor of cardiovascular risk. Objective: This study aimed to analyze the effects of a single session of resistance training on aortic BP in PAD patients. Methods: This randomized, crossover, controlled trial involved 16 patients. All of them performed a session of resistance training (R - 3 x 10 reps in eight exercises, 5-7 on the OMNI Scale) and a control session (C - resting for 50 min). Before and after each session, aortic BP was assessed by applanation tonometry technique. Results: There was an increase in systolic (P<0.002) and mean (P<0.001) aortic BP in both sessions; however, higher increases were observed in C session (P<0.001). Additionally, diastolic aortic BP only increased after C session (P=0.004). The hypotensive effect of the exercise on systolic, diastolic, and mean aortic BP were -12±2, -6±2, and -7±2 mmHg, respectively. Conclusion: A single session of resistance training promoted a hypotensive effect on aortic BP of patients with PAD, indicating an acute reduction in cardiovascular risk in this population. Level of Evidence I; Therapeutic studies - Investigating the results of treatment.